JUARA SATU DAN DUA: MEMBANDINGKAN SITUASI KEBAHASAAN INDONESIA DAN PAPUA NUGINI - René van den Berg (Masyarakat Linguistik Indonesia, 2014)
With 836 and 706 languages each, Papua New Guinea and Indonesia occupy the two top positions in the list of countries with the highest number of languages. This article aims to provide a linguistic comparison of these two neighbouring countries. After a general introduction with some background information about each country, the first part of the article focuses on the national languages (bahasa Indonesia and Tok Pisin), their history and current role, as well as a brief treatment of some lexical and structural features of Tok Pisin. Part one ends with a general discussion of the role of the regional languages in both countries, followed in part two by a more detailed discussion of one Austronesian regional language from each country: Muna from Southeast Sulawesi in Indonesia, and Vitu from West New Britain in Papua New Guinea. This section does not only treat the history and role of these two languages, but also compares various structural features, as well as their level of description and endangerment. The article ends with three brief suggestions.